International Taxation and Productivity Effects of M&As - Maximilian Todtenhaupt; Johannes Voget (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
We investigate the effect of international differences in corporate taxation on the realization of productivity gains in M&A deals. We argue that tax differentials distort the efficient allocation of productive factors following an M&A and thus mitigate the resulting productivity improvement. Using firm-level data on inputs and outputs of production as well as on corporate M&As, we estimate that a 1 percentage point increase in the absolute tax differential between the locations of two merging firms reduces the subsequent total factor productivity gain by 4.5%. This effect is less pronounced when firms can use international profit shifting to attenuate effective differences in taxation. In a complementary analysis, we use an event study design and a fixed effects model to explore the timing of the response of productivity, as well as, labor and capital input to the tax rate differential after the merger separately for the acquirer and the target. We show that our findings are mainly driven by deals with targets residing in locations with a tax advantage with respect to the acquirer. In these transactions, tax differentials reduce the post-merger adjustment in the target firm and inhibit the full realization of productivity gains.
Keywords: F23; G34; H25; D24; 330; M&A; productivity; international taxation